Beyond Technocratic Quality: Toward an Islamic TQM Model for Holistic Educational Management - Tobroni Tobroni; Kadar Risman; Faridi Faridi; Ahmad Saefullah (Universitas Nurul Jadid, 2025)
This study examines the integration of Total Quality Management (TQM) and Islamic spiritual values in educational quality management. The study aims to develop a conceptual model of Islamic TQM as a holistic quality management framework for Islamic educational institutions. A qualitative approach with a library research design was employed. Data were collected from reputable journal articles, academic books, and scientific publications related to TQM, spiritual leadership, Islamic quality management, and Islamic education management. The data were analyzed using thematic analysis through four stages: data extraction, open coding, axial coding, and selective coding. The findings reveal four major themes: (1) the dominance of a technocratic TQM paradigm focused on efficiency and standardization; (2) spirituality as an internal dimension that enhances organizational commitment and performance; (3) Islamic values such as tauhid, amanah, ihsan, and itqan as normative foundations of quality management; and (4) the integration of TQM principles and Islamic values into a holistic management model. The study concludes that the proposed Islamic TQM model provides a more comprehensive framework by combining managerial effectiveness, moral responsibility, and spiritual orientation. This model is relevant for madrasah, pesantren, and Islamic higher education institutions in responding to contemporary educational challenges.